A walk in the woods: the effects of ethnicity, social class, and gender among urban Norwegian adolescents - Tore Bjerke; Olve Krange (Nordic Journal of Social Research)
Objectives:  The main objective was to study the influences of gender, ethnicity, and socioeconomic factors on a popular Norwegian outdoor activity: walking in the woods.